2021
DOI: 10.1088/1755-1315/930/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Rice Straw Mulch on Surface Runoff and Soil Loss in Agricultural Land Under Simulated Rainfall

Abstract: Installation of mulch on agricultural land, besides reducing weed growth, can also protect the soil surface from rain and erosion. This study aims to determine the effectiveness of rice straw mulch in reducing surface runoff and soil loss before entering the river. The experimental soil materials were similar to those in Sumber Brantas village, Bumiaji Sub-District, Batu. Runoff modelling utilized the Armfield S12 Rainfall Simulator - Advanced Environmental Hydrology System, with rainfall of 1 and 1.7 l/min. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…For this study, the utilized daily annual maximum rainfall data were from 2008-2020 and taken from the nearest rain station, the Junggo rain station in Bumiaji Sub-District, Batu. The maximum rainfall was 105 mm (1.96 l/minute), while the minimum rainfall was 64 mm (1.2 l/minute) (Haribowo, Asmaranto, Kusuma, & Amrina, 2021). Due to the limitations of the rainfall simulator, there was a decrease of rainfall intensity in the model by 13%.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this study, the utilized daily annual maximum rainfall data were from 2008-2020 and taken from the nearest rain station, the Junggo rain station in Bumiaji Sub-District, Batu. The maximum rainfall was 105 mm (1.96 l/minute), while the minimum rainfall was 64 mm (1.2 l/minute) (Haribowo, Asmaranto, Kusuma, & Amrina, 2021). Due to the limitations of the rainfall simulator, there was a decrease of rainfall intensity in the model by 13%.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the modeling was carried out at the Hydrology Laboratory of the Department of Water Resources Engineering in Universitas Brawijaya, Indonesia. Rainfall modeling utilized Armfield's S12 Advanced Environmental Hydrology System Rainfall Simulator tool (Armfield, 2021;Haribowo, Asmaranto, Kusuma, & Amrina, 2021;Yao, 2020) (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Retaining soil moisture causes the soil particles to stick together and maintain their close packing. When soil runoff gets reduced, soil erosion is prevented (Haribowo et al 2021). Due to nutrient cycling, the process of mulching the soil probably improves the soil's nutrient status.…”
Section: Significant Effects Of Organic Mulchmentioning
confidence: 99%
“…Studies conducted by Tiquia et al (2002) demonstrated that mulching enhanced the SOM and P content of the soil. Thus, mulching increases soil nutrient content by preventing nutrient loss (Haribowo et al 2021). Farmers can produce high-quality food in big quantities because of this technology.…”
Section: Significant Effects Of Organic Mulchmentioning
confidence: 99%